1962
DOI: 10.1115/1.3657252
|View full text |Cite
|
Sign up to set email alerts
|

The Magnetohydrodynamic Slider Bearing

Abstract: An analysis is presented of the slider bearing using an electrically conducting lubricant, such as a liquid metal, in the presence of a magnetic field. The solution permits the calculation of the load-carrying capacity of the bearing. A comparison is made with the classical slider bearing solution. It is shown that the load capacity of the bearing depends on the electromagnetic boundary conditions entering through the conductivity of the bearing surfaces. Numerical data are presented for nonconducting surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1965
1965
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In this technology, the pressurized working fluid in the closed cycle EFGT is used as lubricant and coolant for the bearings. Magneto-hydrodynamic (MHD) bearings with conductive lubricant material were studied elaborately in the early 1960s [101][102][103][104]. However, magnetic bearings with no required conductive lubricant is more practical and best suited for the HTR closed cycle EFGT.…”
Section: Gas Turbine Lubrication Systemmentioning
confidence: 99%
“…In this technology, the pressurized working fluid in the closed cycle EFGT is used as lubricant and coolant for the bearings. Magneto-hydrodynamic (MHD) bearings with conductive lubricant material were studied elaborately in the early 1960s [101][102][103][104]. However, magnetic bearings with no required conductive lubricant is more practical and best suited for the HTR closed cycle EFGT.…”
Section: Gas Turbine Lubrication Systemmentioning
confidence: 99%
“…Because of the industrial necessity for bearings design, many authors have investigated the MHD slider-bearing performance using conducting Newtonian lubricants and applying a uniform transverse magnetic field. For example, Snyder (1962), Hughes (1963a), Lin et al (2009) studied infinite inclined plane slider bearing, Hughes (1963b) investigated finite step slider bearing, Lin (2003) and Kesavan et al (2014) considered finite rectangular plates. These studies found that increasing the external magnetic field strength increases load-bearing capacity compared with the nonmagnetic case.…”
Section: Introductionmentioning
confidence: 99%
“…The study of dynamics of flow of electrically conducting fluid with the application of magnetic field is known as magnetohydrodynamic (MHD). Several investigators were studied the effect of applied magnetic field on the performance of bearings such as lubrication of bearing in the presence of magnetic field by Agarwal , slider bearing by Snyder , squeeze film by Hazma and finite slider bearings by Lin . They concluded that the applied magnetic field increases the load carrying capacity and decreases the frictional force.…”
Section: Introductionmentioning
confidence: 99%